ELIMINATION OF BIOFILM PRODUCED BY ESCHERICHIA COLI AFTER EXPOSURE TO STRONTIUM SR90 AND CESIUM CS137 RADIOACTIVE SOURCE IN DIFFERENT DOSES - Mohammed, Nebras Rada (Journal of Medical Genetics and Clinical Biology, 2024)
Objective:. The purpose of this research in order to remove biofilm produced from E. coli with different radioactive sources.Study design: Case–control in analytical and cross-sectional in descriptive study design. Backgrounds: The bacterium E. coli which is pathogenic to the urinary tract, depends on a wide number of virulence determinants, as it is the most important bacterium responsible for urinary tract infections. Radiation is power in the appearance of undulations or spout of mote. There are several types of radiance overall concerning us. Alpha dissolution occurs while the mote throw of the nucleus that constitute of two no and two P+. Beta dissolution a no is convert a P+ and an e- is released of the nucleus. Gamma dissolution happen through residuum power in the nucleus next alpha or beta dissolution or subsequent no catch (a kind of atomic response) in a nuclear reactor. Methodology: Study populations and bacterial isolates with diagnosing E. coli from catheter and several diseases from patients in Baghdad hospitals in 2023/ 2024. Expose the bacteria to radiance released of Sr90 and CS137 radioactive sources in various doses with screening biofilm production before and after exposure to radiation. Results: The results show that there is a high killing rate of E. coli during exposure to Cesium-90 and Cesium-137 radioactive sources. As well as loss of biofilm production at different doses. Conclusion: Firstly, the impact of radiance of various radioactive sources occasion the homicide of E. coli. Secondly, the impact of radiance released of radioactive sources in various doses is analogous in homicide of E. coli.